The Concept of Islamic Education by Abuddin Nata: Relevance and Application in Contemporary Islamic Education - Asafila, Ina Machla; Maragustam, Maragustam (Program Studi Aqidah dan Filsafat Islam, 2024)
This research delves into the comprehensive and adaptable concept of Islamic education as articulated by Abuddin Nata. The study aims to explore Abuddin Nata’s biography, his perspectives on Islamic education, and their relevance to contemporary Islamic educational practices. Employing a qualitative approach, specifically library research, this study draws from primary sources—books authored by Abuddin Nata—and secondary sources, including relevant books and journals. The analysis method employed is descriptive-analytical. The findings reveal that Abuddin Nata’s proposed Islamic education aligns with perennialist principles, emphasizing universality, balance, clarity, realism, and dynamism. These principles ensure that Islamic education remains steadfast in its core values, objectives, and distinctive features, despite societal changes. Abuddin Nata’s concept underscores a holistic and comprehensive approach grounded in divine values, making it relevant across different epochs. This study also highlights the alignment of Abuddin Nata's principles with modern educational frameworks, such as character education and competency-based curricula, showcasing their continued relevance.